Global View on the Cytokinin Regulatory System in Potato - Lomin, Sergey N.; Myakushina, Yulia A.; Kolachevskaya, Oksana O.; Getman, Irina A.; Savelieva, Ekaterina M.; Arkhipov, Dmitry V.; Deigraf, Svetlana V.; Romanov, Georgy A. (Frontiers in Plant Science, 2020)
Cytokinins (CKs) were earlier shown to promote potato tuberization. Our study aimed to identify and characterize CK-related genes which constitute CK regulatory system in the core potato (Solanum tuberosum) genome. For that, CK-related genes were retrieved from sequenced genome of the S. tuberosum doubled monoploid (DM) Phureja group, classified and compared to Arabidopsis orthologs. Analysis of selected gene expression was performed with transcriptome database for the S. tuberosum heterozygous diploid line RH89-039-16. Genes responsible for CK signaling, biosynthesis, transport and metabolism were categorized in an organ-specific fashion. According to this database, CK receptors StHK2/3 predominate in leaves and flowers, StHK4 in roots. Among phosphotransmitters, StHP1a expression largely predominates. Surprisingly, two pseudo-phosphotransmitters, intended to suppress CK effects, are hardly expressed in studied organs. Among B-type RR genes, StRR1b, StRR11 and StRR18a are actively expressed, with StRR1b expressing most uniformly in all organs and StRR11 exhibiting the highest expression in roots. By cluster analysis four types of prevailing CK-signaling chains were identified in: 1) leaves and flowers, StHK2/3>StHP1a>StRR1b/+; 2) shoot apical meristems, stolons and mature tubers, StHK2/4>StHP1a>StRR1b/+; 3) stems and young tubers, StHK2/4>StHP1a>StRR1b/11/18a; 4) roots and tuber sprouts, StHK4>StHP1a>StRR11/18a. CK synthesis genes StIPT3/5 and StCYP735A are expressed mainly in roots following by tuber sprouts, but rather weak in stolons and tubers. By contrast, CK-activation genes StLOGs are active in stolons, and StLOG3b expression is even stolon-confined. Apparently, main CK effects on tuber initiation are realized via activity of StLOG1/3a/3b/7c/8a genes in stolons. Current advances and future directions in potato research are discussed.